THU0390 Prolonged disease-free interval in familial mediterranean fever: A distinct subset with unique clinical, demographic and molecular characteristics. (23rd January 2014) - Ben-Zvi, I.; Krichely-Vachdi, T.; Feld, O.; Lidar, M.; Kivity, S.; Livneh, A.
Abstract : Background: Familial Mediterranean fever (FMF) is a genetic, autoinflammatory disease, characterized by episodes of fever and serosal or cutaneous inflammation. Between the attacks, patients are usually asymptomatic, but subclinical inflammation may persist. A rare and under-recognized phenomenon in FMF is prolonged disease-free intervals (of 3 years or more), even without colchicine treatment. Objectives: We aimed to clinically, genetically and demographically characterize FMF patients with prolonged disease-free intervals during the course of the disease. Methods: Over a 5 year period, 1000 FMF patients, coming to their regular follow up visit, were screened for prolonged disease-free interval (≥3 years) occurring sometime along the course of their disease. Clinical, demographic and genetic parameters of the patients identified were compared to those of randomized selected control subjects, derived from the same patient population. The severity of the disease was determined using the Mor severity score Results: Thirty three patients with prolonged disease-free interval (remission) were identified (3.3% of the screened population). Compared to the 33 control subjects, in patients with long term remission the disease was of milderseverity (23 vs 11 patients with mild disease in the remission and control groups, respectively, p=0.003) and with longer diagnosis delay (21 vs 13.4 years, p=0.04). Patients with long term remission presented mostly with abdominal attacks, low rate of attacks in other sites and low rate of chronic and non-attack manifestations. The disease in patients with long term remission responded well to colchicine, despite using a lower dose (p<0.001). None of the patients in the remission group were homozygous for the M694V mutation compared to 10 in the control group (p=0.0008) Conclusions: Long-term remission defines a rare and milder form of FMF with unique clinical, demographic, and molecular characteristics. Disclosure of Interest: None Declared